Verification of AOCS Cd 29a-13: 2013 Method for 3-Chloropropane-1.2-Diol Esters and Glycidol Esters Analysis in Palm Oil - Zada Agna Talitha; Nuri Andarwulan; Didah Nur Faridah (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2020)
Fatty acid esters of 3-Chloropropane-1,2-diol (3-MCPD) and Glycidol were contaminants in fat-rich foods such as palm oil. These contaminants have received serious concern since they may cause cancer in humans. Several methods have been developed to analyze 3-MCPDEs and GEs especially in refined palm oil, including AOCS Cd 29a-13 2013 with aid of GC-MS. Principally, it involves transesterification promoted by H2SO4 in MeOH, then derivatized using PBA (Phenylboronic Acid). The verification was required before applying this method in laboratory. The instrument performance analysis showed that linearity response (r) reaching up to 0.997 for 3-MCPD and 0.998 for Glycidol, determined from a linear regression using internal standards and external standards at the range of 0.3-9.3 mg/kg (3-MCPD) and 0.6-21.3 mg/kg(Glycidol). The precision of retention time in 3-MCPD and Glycidol demonstrated satisfying results, RSD = 0,03% (3-MCPD-d5), RSD = 0,02% (3-MCPD), RSD = 0.03% (Gly-d5) and RSD = 0.03% (Glycidol). The LoD was observed at 0.037 mg/kg (3-MCPD) and 0.072 mg/kg (Glycidol), while the LoQ was found at 0.123 mg/kg (3-MCPD) and 0.241 mg/kg (Glycidol). The verification method showed that recovery percentage for 3-MCPD and Glycidol was 92.19% and 88.38%. The precision of retention time results, RSD = 0.05% (3-MCPD) and RSD = 0.04% (Glycidol) and the precision of concentration results showing RSD Analysis value?<2/3 RSD Horwitz. Within the RSD analysis of lab reproducibility was obtained at 3.42% (3-MCPD) and 3.64% (Gly) less than the value of RSDh. This method also have a good specificity. Based on the verification results, this method meets all requirements and therefore can be applied for analysis in the laboratory.